2010
DOI: 10.1038/nature08942
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spin liquid emerging in two-dimensional correlated Dirac fermions

Abstract: At sufficiently low temperatures, condensed-matter systems tend to develop order. A notable exception to this behaviour is the case of quantum spin liquids, in which quantum fluctuations prevent a transition to an ordered state down to the lowest temperatures. There have now been tentative observations of such states in some two-dimensional organic compounds, yet quantum spin liquids remain elusive in microscopic two-dimensional models that are relevant to experiments. Here we show, by means of large-scale qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
793
7
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 603 publications
(857 citation statements)
references
References 51 publications
48
793
7
9
Order By: Relevance
“…For limiting cases, we have performed unrestricted Hartree-Fock calculations for multi-orbital Hubbard models defined on (111) bilayers. We found that the TI states are rather robust for e g 2 systems and become unstable against antiferromagnetic insulating states when the interaction strength is comparable to the full bandwidth as in the 2D Hubbard model on the honeycomb lattice 52 . For e g 1 or e g 3 systems, the QAH-insulating states could be generated dynamically by correlation effects without the SOC 53,54 , yet trivial-insulating states due to the Jahn-Teller effect would also be stabilized depending on the relative balance between the Coulomb interaction and the Jahn-Teller coupling.…”
Section: Discussionmentioning
confidence: 79%
“…For limiting cases, we have performed unrestricted Hartree-Fock calculations for multi-orbital Hubbard models defined on (111) bilayers. We found that the TI states are rather robust for e g 2 systems and become unstable against antiferromagnetic insulating states when the interaction strength is comparable to the full bandwidth as in the 2D Hubbard model on the honeycomb lattice 52 . For e g 1 or e g 3 systems, the QAH-insulating states could be generated dynamically by correlation effects without the SOC 53,54 , yet trivial-insulating states due to the Jahn-Teller effect would also be stabilized depending on the relative balance between the Coulomb interaction and the Jahn-Teller coupling.…”
Section: Discussionmentioning
confidence: 79%
“…The findings of Ref. [82] have been recently addressed in Ref. [83], by QMC simulations of the same model in larger clusters (containing up to 2592 sites), finding very weak evidence of a spin liquid phase.…”
Section: Hubbard Correlations and Split Bandsmentioning
confidence: 87%
“…Early on it was shown that at half filling and for U/t > ∼ 5 a semimetal-Mott insulator transition occurs [81]. Recently, a QMC calculation has demonstrated [82] the existence of a gapped antiferromagnetic phase for U/t > 4.3 and presented evidence for a gapped spin liquid phase in the range of couplings 3.5 < U/t < 4.3. The findings of Ref.…”
Section: Hubbard Correlations and Split Bandsmentioning
confidence: 99%
“…For example, magnetism has experimentally been reported both in nanographene [58,59,60], and in graphite in the presence of disorder [61] or grain boundaries [62], although pristine graphene has not been found to be either magnetic [63] or gapped [64,20]. Theoretically, on-site Coulomb repulsion exceeding U > 3.9t has been found to give an antiferromagnetic state in undoped graphene in quantum Monte Carlo simulations [15,17]. This relatively large value of U is a consequence of undoped graphene being a semimetal with only a point-like Fermi surface.…”
Section: Electron Interactions In Graphenementioning
confidence: 99%
“…A large number of exotic states of matter has been proposed theoretically, see e.g. [4,5,6,7,8,9,10,11,12,13,14,15,16,17], but most have not been experimentally observed as of yet. One exception is multi-layer graphene systems where there are now experimental reports of an energy gap opening at low temperatures, which has been ascribed to interactions effects [18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%